Effects of cashew leaf extract on physicochemical, antioxidant, and antimicrobial properties of N, O–Carboxymethyl chitosan films - P.P. Nadira; V.M.Abdul Mujeeb; P.Mujeeb Rahman; K. Muraleedharan (Carbohydrate Polymer Technologies and Applications, 2022)
The aim of this study was to investigate the influence of cashew leaf extract on the physicochemical, antioxidant, and antimicrobial properties of carboxymethyl chitosan (CMC) films. Active films of CMC were prepared by incorporating different concentrations (5, 10, 15, and 20%) of cashew leaf extract. The films thus obtained were characterized by FTIR, UV-Visible spectroscopy, SEM, and TGA. The moisture content and water solubility of the films were determined and found that their value reduced with an increase in the amount of leaf extract. The inclusion of leaf extract improved the opacity (0.69–5.06) and tensile strength (21.16–31.47 MPa) of CMC. The antioxidant and antimicrobial properties of all the prepared films were examined. A concomitant increase in antioxidant activity was noticed with the increase in the concentration of leaf extract. With the addition of 20% leaf extract, the antioxidant activity of CMC film was found to increase by six times. Modified CMC films were excellent antimicrobials. They furnished significant (P < 0.05) progress in antimicrobial activity against Escherichia coli and Staphylococcus aureus on an average of 72 and 81% respectively. Hence these films can be envisaged as a potential material for food packaging.